PLANT GROWTH PROMOTION AND YIELD IMPROVEMENT BY BACILLUS PRODUCTS ON GROUNDNUT IN QUANG NAM PROVINCE - Vu, Nguyen Xuan; Cuong, Le Nhu; Nhi, Phan Thi Phuong; Lam, Le Duc (Hue University Journal of Science: Natural Science, 2018)
Beneficial bacteria such as Bacillus promote the plant growth through several mechanisms such as growth stimulators, dissolving insoluble chemical compounds, inducing systematic disease resistance, and suppressing diseases. In this study, six bacillus bio-products, namely BaD-S1A1, BaD-S1F3, BaD-S13E2, BaD-S13E3, BsD-S18F11, BaD-S20D12, which were produced from Bacillus strains isolated from peanuts in central Vietnam, were evaluated for their ability to promote the growth and improve the peanut yield on sandy loam soil in Quang Nam province in the Summer season 2017. The bacillus products were applied to the soil at sowing time at the rate of 1 g bacillus product (109 cfu·g–1) per one square metre. The results showed that some bacillus products increased the seed emergence, promoted the plant growth and increased the peanut yield. The increase of the groundnut yield ranged from 6.4 to 18.3 % compared with the control.